If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -3 = 3x + -15 Reorder the terms: -3 + 1x = 3x + -15 Reorder the terms: -3 + 1x = -15 + 3x Solving -3 + 1x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + 1x + -3x = -15 + 3x + -3x Combine like terms: 1x + -3x = -2x -3 + -2x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -2x = -15 + 0 -3 + -2x = -15 Add '3' to each side of the equation. -3 + 3 + -2x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = -15 + 3 -2x = -15 + 3 Combine like terms: -15 + 3 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| x+.5x+.75x=100 | | 4-(x-3)=5x+1 | | 3x+2x+(x+12)+(2x+4)=180 | | x+5=-4x+10 | | FV=1800(1.00667)24 | | 2(3p-4)-3(5-2p)+18=19 | | 0.77= | | 2(3P-4)-3(5-29)+18=19 | | -4x+6=2x+2 | | 2b=-6 | | 5(2x-1)=6x+2 | | 96=1x*10 | | 114-6x=9x-4 | | -2(1+2v)=25+5v | | -8+0=-8 | | b/8-7=8 | | 5=6(9-5)19 | | 85=5x+7y | | 7-4a(d-3)=23 | | 2x-1y=-5 | | 61.50/1/3 | | 6/9=-4t/27 | | C=a+2bfora | | 26x+10x=100 | | 40-2(a+9)=6 | | 4(-2+5n)-4n=24+8n | | 0.09d-14=0.67 | | 2x^2-36=8 | | 25(1-x)=8x-9 | | 15-6w=4w-7 | | -8(1+7m)=-8m+40 | | (-5x+6)/10=5.6 |